Tolerability and camouflaging effect of corrective make-up for acne: results of a clinical study of a novel face compact cream - Monfrecola G; Cacciapuoti S; Capasso C; Delfino M; Fabbrocini G (Dove Medical Press, 2016)
Giuseppe Monfrecola, Sara Cacciapuoti, Claudia Capasso, Mario Delfino, Gabriella Fabbrocini Department of Clinical Medicine and Surgery, Section of Dermatology, University of Naples Federico II, Naples, Italy Background: A novel face compact cream (FCC) containing a new patented formulation was recently developed to provide acne patients with cosmetic camouflage for their lesions and to have beneficial effects on the multifactorial components of the disease. This pilot investigation aimed to evaluate the real-life tolerability, potential for comedogenicity and covering effect provided by this FCC.Methods: This single-center study evaluated the FCC applied once daily for 28 days in 20 females with facial acne. Tolerability was assessed by rating skin reactions on a scale from 1 =absent to 4 =evident. Comedogenicity potential was evaluated by determining the number of facial acne lesions before and after use of the FCC. The covering effect was rated in ten patients 30 minutes after application on a scale from 1 =none to 5 =excellent. Patients rated their opinions on the FCC on day 28 using a questionnaire.Results: Assessment of tolerability on days 0, 14, and 28 showed that skin reactions, including erythema, edema, dryness, desquamation, tight feeling, itching, and burning, were absent in all patients. The FCC was noncomedogenic and provided a significant 15.8% reduction in facial acne lesions after 28 days (P<0.001). The FCC provided a good covering effect 30 minutes after application in 80% of patients. All patients (100%) were satisfied with the FCC, with 90% agreeing that the FCC was effective and 80% stating that the FCC improved their skin.Conclusion: The FCC was positively perceived, well tolerated, noncomedogenic, and provided an effective covering of acne in this small group of female patients with 1 month of follow-up. Keywords: acne, comedones, dermatocosmetic, tolerability